2017
DOI: 10.5194/tc-11-891-2017
|View full text |Cite
|
Sign up to set email alerts
|

Determination of snowmaking efficiency on a ski slope from observations and modelling of snowmaking events and seasonal snow accumulation

Abstract: Abstract. The production of Machine Made (MM) snow is now generalized in ski resorts and represents the most common method of adaptation for mitigating the impact of a lack of snow on skiing. Most investigations of correlations between snow conditions and the ski industry's economy focus on the production of MM snow though not one of these has taken into account the efficiency of the snowmaking process. The present study consists of observations of snow conditions (depth and mass) using a Differential GPS meth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 35 publications
2
31
0
Order By: Relevance
“…The two studies identified a huge range of potential water losses (0-59%). Moreover, the losses for air-water guns (snow lances) reported by Olefs et al (2010) and the results from Spandre et al (2017) strongly differ. Besides the temperature regression of Eisel et al (1988), correlations between mass loss and meteorological settings have not been investigated.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…The two studies identified a huge range of potential water losses (0-59%). Moreover, the losses for air-water guns (snow lances) reported by Olefs et al (2010) and the results from Spandre et al (2017) strongly differ. Besides the temperature regression of Eisel et al (1988), correlations between mass loss and meteorological settings have not been investigated.…”
Section: Introductionmentioning
confidence: 81%
“…They concluded that only 25-50% of the water used for snow-making was finally recovered as snow on the ski runs. Recently, Spandre et al (2017) presented results of mass balance measurements collected during operational snowmaking in a French ski resort. During five snow-making sessions performed in November and December, 41-89% of the snow could be detected in a 20 m circle surrounding the peak of the accumulation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In low elevation ski areas, snow making represents a key technology to buffer the impact of interannual variability of snow conditions, and is increasingly considered to be the most reliable adaptation measure for alpine ski resorts facing the consequences of climate change (Uhlmann et al, 2009;Spandre et al, 2017). However, for successful and efficient production of machine-made snow, particular air temperature and humidity conditions need to be met, generally defined by a wet bulb temperature (Twb) threshold.…”
Section: Introductionmentioning
confidence: 99%